Impactos socioambientais da eucaliptocultura e avaliação da toxicidade da água de decomposição das folhas de Eucalyptus urophylla S.T. Blake (Myrtaceae) em Allium cepa L. (Amaryllidaceae) - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
Commercial interest increases the large-scale production of Eucalyptus spp. outside their home environment. Associated with this expansion of eucalyptus culture are the positive and negative impacts of production. The contribution with the trade balance, native forest preservation and carbon sequestration stand out as benefits. On the other hand, the negative impacts include socioenvironmental problems, water quality and availability, soil quality, biodiversity reduction and toxic effect of the compounds released by the plant. In the first chapter, this research aimed to compile qualitative and quantitative data on the impacts caused by eucalyptus plantations, and in the second chapter to evaluate the toxicity of the decomposition water of leaves of Eucalyptus urophylla S.T. Blake (Myrtaceae) on Allium cepa L. (Amaryllidaceae). With subsidy in the literature it can be inferred that the scientific production regarding the impacts caused by eucalyptus culture from 2008 to 2018 is still incipient. Most research evaluates the impacts on soil quality and a tiny amount on biodiversity and social problems, a matter of concern through the expansion of production. It was found 32 compounds released during the different treatments of decomposition and leaf extract, by gas chromatography coupled to mass spectrometry (GC-MS). The compounds 2- ethyl-1-hexanol, fenchone, cis-dihydrocarvone, and trans-dihydrocarvone appeared in the decomposing water of the leaves at all periods but were absent in the leaf extract. However, compounds such as eucalyptol, α-pinene and α-terpinyl acetate were only present in the extract. The compounds are part of the classes of monoterpenes, sesquiterpenes, triterpenes and others. As for toxicity, the effect was verified by inhibition of the root growth of Allium cepa, identified after exposure of the roots to different concentrations of water of decomposition of eucalyptus leaves in different periods. For cytotoxicity, assessed by histological cutting of the exposed roots at different concentrations and periods of decomposition, the results were not sufficient to indicate the toxic effect. However, some mutations and cell death and morphological changes in the roots of Allium cepa were identified. Academic production on the impacts of eucalyptus production in the last ten years has been low, especially considering that eucalyptus cultivation has grown annually, it is necessary that more studies are produced on the impacts of this monoculture on a large scale, mainly related to social and environmental impacts. The compounds released by the leaves of E. urophylla during decomposition in water show a toxic effect evidenced by the inhibition of the root growth of Allium cepa, being higher in the first 10 days.
Socio-environmental impacts of eucaliptoculture and evaluation of the toxicity of decomposition water of Eucalyptus urophylla S.T. Blake (Myrtaceae) in Allium cepa L. (Amaryllidaceae)
Keywords: Aleloquímicos; Ecotoxicidade; Bioensaio; Allochemicals; Ecotoxicity; Bioassay; CIENCIAS BIOLOGICAS